A simple method for unbiased estimating of ejaculated sperm tail length in subjects with normal and abnormal sperm motility - Noorafshan, Ali; Karbalay-Doust, Saied (Micron (Oxford, England : 1993), 2010)
The tail of a spermatocyte is one of the important factors determining the propulsive velocity of the cell and hence the potential the cell has to achieve fertilization. Stereological estimation of the length of sperm's tail has received little attention and mainly the length of the tail has mainly been estimated using image analyzers or tracing method on the electron or light microscopic samples. The aim of this study is to present a description of the stereological method for sperm's tail length estimating and comparison of sperm's tail length in subjects with normal and abnormal sperm motility. The semen samples were analyzed and 14 semen samples were selected. If more than 50% of spermatozoa were graded as nonprogressive motility and immotility (according to WHO criteria) it was considered as abnormal motility. Seven sperm samples were selected from the normal subjects. The smear samples were stained. The sperm's tail length was estimated by counting the number of intersections between the tails and Merz grid test line in an unbiased counting frame, superimposed on live images of sperms. The data showed that the length of sperm's tail was on average ∼51% lower in subjects with abnormal sperm motility in comparison with the normal subjects. The method presented here seems to be a useful and very efficient way to estimate the lengths of randomly orientated sperms’ tails and detect the effects of various substances on the tail length. The data support that the sperm's tail length is significantly shorter in subjects with abnormal motility compared with the controls.